Approaches about the expression of two MADS-box genes in pear during the seasonal leaf bud-dormancy transitional phases in the subtropical climate - Leivas, Gabrielle; Klumb, Elsa Kuhn; Bianchi, Valmor João; Yamamoto, Robson Ryu; Amarante, Luciano de; Pereira, José Francisco Martins; Herter, Flávio Gilberto; Chaves, Ana Lúcia Soares; Mello-Farias, Paulo Celso de (Bragantia, 2022)
ABSTRACT In the last decades, several biochemical and molecular studies in pear (Pyrus spp.) have revealed processes associated with dormancy establishment and release, leading to the identification of several MADS-box family genes related to bud dormancy regulation. Thus, the aim of this study was to evaluate a preliminary expression pattern of the PpDAM13-1 and PpDAM13-2 MADS-box genes in pear leaf buds (Pyrus pyrifolia Nakai, cultivars Hosui and Nijisseiki; and Pyrus communis L., cultivars Rocha and Santa Maria), grown in the subtropical climate of Southern Brazil. Lateral leaf buds were collected from June to September, and RNA was extracted for evaluation of gene expression by reverse transcription polymerase chain reaction (RT-qPCR). It was found that these two genes decreased the expression as leaf buds are release from dormancy. The Hosui cultivar for both genes and the Nijisseiki cultivar for PpDAM13-2 gene showed peaks of expression in early June, indicating that leaf buds are in a transition dormancy phase. The two European cultivars showed this transition dormancy phase between the end-July and the mid-August. It was concluded that the expression analysis of PpDAM13-1 and PpDAM13-2 genes can be used as a marker to evaluate changes of dormancy phase in pear trees in subtropical climate conditions, and it can be suitable to assist management strategies for overcoming pears’ bud dormancy.